Factors associated with breast self-examination among women of reproductive age in Lampung-Indonesia - Sri Diastuti; Wayan Aryawati; Nurul Aryastuti (Malahayati International Journal of Nursing and Health Science, 2023)
Background: Breast cancer in Indonesia ranks first with 68,858 cancer cases and the second cause of cancer-related deaths with 22,430. In 2020 in Lampung Province there were 980 cases of breast lumps and 246 cases of breast cancer while in North Lampung district there were 26 cases of breast lumps and 7 cases of suspected breast cancer. The Abung Kunang Health Center had 3 cases of lumps in the breast and 2 cases of suspected breast cancer. Cancer prevention is a priority through Breast Self-Examination (BSE).Purpose: To determine the factors associated with breast self-examination (BSE) in women of productive age (WCA) at the Abung Kunang Community Health Center, North Lampung Regency in 2023.Method: Quantitative with cross sectional design. The population in this study were women of childbearing age aged 15-49 years who were at the Abung Kunang Community Health Center in North Lampung Regency in 2022 with a total of 381 samples. The sample technique used is multi-stage random sampling. Data analysis in this study used univariate, bivariate (chi-square), and multivariate (multiple logistic regression).Results: Shows that there is a relationship between knowledge (p value 0.000 and OR 3.147), attitude (p value 0.004 OR 1.900), education (p value 0.015 and OR 1.736), support from health workers (p value 0.014 and OR 1.708) and exposure to information media (p value 0.015 and OR 3.054) and there is no relationship between family support and BSE implementation in women of childbearing age. The most related factor is knowledge with (p value 0.000 and OR 2.567). It is hoped that health workers can provide implementation demonstrations and carry out community empowerment such as IT (information and technology) training.Conclusion: Factors related to the implementation of breast self-examination (BSE) in dealing with the occurrence of breast cancer, namely knowledge, attitudes, education, family support, health workers, and exposure to information media from respondents. However, from these factors the most related at the Abung Kunang Health Center in North Lampung Regency in 2023 is knowledge with OR 2.567.